How Do Trust and Convenience Build Long-Lasting Loyalty? A Study of Muslim Female Gen-Z on Shopee - Zulfiani, Ika; Nurfitriani, Nurfitriani; Nursyamsu, Nursyamsu; Salmita, Dewi; Alkhazaleh, Salameh (Faculty of Economics and Management, 2025)
Thi s study aims to understand how trust and convenience can build long-lasting customer loyalty among Muslim Female Generation-Z users on the Shopee app, with customer satisfaction as the key moderating factor in this relationship. This research is a descriptive-analytical study. The total population consists of 826 respondents, with a purposive sampling technique employed. Using the Slovin formula, a sample of 89 respondents was obtained. Data collection was conducted through questionnaires, and the data analysis techniques employed include validity testing, reliability testing, classical assumption testing, multiple regression analysis, hypothesis testing, Moderated Regression Analysis (MRA), and determination testing. Using a quantitative approach, data were collected through questionnaires from Muslim Female Generation-Z respondents and analyzed using SPSS. The findings reveal that both trust and convenience significantly contribute to increased customer loyalty, with customer satisfaction strengthening this relationship. This study offers new insights into the importance of building trust and providing convenience to create a satisfying and sustainable shopping experience for Muslim Female Generation-Z users. Consequently, these findings highlight key factors that e-commerce platforms should consider to retain customer loyalty, particularly among young Muslim women.